2023
DOI: 10.3390/nu15102252
|View full text |Cite
|
Sign up to set email alerts
|

Diet and Exercise Exert a Differential Effect on Glucose Metabolism Markers According to the Degree of NAFLD Severity

Abstract: Background: Non-Alcoholic Fatty Liver Disease (NAFLD) and Type 2 Diabetes (T2D) are highly prevalent diseases worldwide. Insulin Resistance (IR) is the common denominator of the two conditions even if the precise timing of onset is unknown. Lifestyle change remains the most effective treatment to manage NAFLD. This study aimed to estimate the effect of the Low Glycemic Index Mediterranean Diet (LGIMD) and exercise (aerobic and resistance) over a one-year period on the longitudinal trajectories of glucose metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Specifically, we showed that the combination of LGIMD and aerobic PA is the most effective treatment for individuals with NAFLD [ 16 ]. In addition, we highlighted the effect of combined PA and LGIMD on glucose metabolism parameters at different grades of NAFLD severity [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we showed that the combination of LGIMD and aerobic PA is the most effective treatment for individuals with NAFLD [ 16 ]. In addition, we highlighted the effect of combined PA and LGIMD on glucose metabolism parameters at different grades of NAFLD severity [ 17 ].…”
Section: Introductionmentioning
confidence: 99%